APLLYING ATA ERROR CATEGORIES TO ANALYZE ENGLISH TRANSLATION OF MUSEUM SANDI YOGYAKARTA’S EXHIBITION LABELS - Dyah Raina Purwaningsih; Maysa Kamilia; Asrofin Nur Kholifah (Language Horizon: Journal of Language Studies, 2025)
As one of the popular educational destinations, the museum attracts both local and foreign visitors who are eager to learn about the country’s cultural heritage and history. Therefore, it is crucial to have translations in other languages, particularly in English. As a global language, English translations can greatly assist foreign visitors in comprehending the content. Unfortunately, there are some cases where translation errors appear in the exhibition labels in museums, affecting the translation accuracy and leading to confusion for the readers. This study aims to identify the types of translation errors on the exhibition labels of Museum Sandi Yogyakarta. This study used qualitative descriptive methods, including observation and data collection. Based on the result, there are 10 translation errors out of 24 types, according to ATA’s Framework for Standardized Error Making. The most prominent types were found in usage and punctuation errors, occurring 18 times for both cases. The errors were mainly influenced by the translator's negligence, carelessness, and a lack of research regarding the rules in the target language.